COVID 19 Vaccination strategies in India- A Public Health perspective - Priyanka; Arora, Ekta; Debbarma, Shibajee; Rasania, Sanjeev Kumar (Indian Journal of Community Health, 2021)
COVID-19 has emerged as one of the most challenging pandemics of the recent times. Although physical-distancing and other transmission-mitigation strategies have helped battling this virus in the most effective way, but this will also paradoxically leave the population without immunity to COVID-19 and thus susceptible to additional waves of infection. Thus, to return to pre-pandemic normalcy, safe and effective vaccination programme is required globally with robust vaccination strategies. This article pens down the important strategies being implemented globally for successful vaccination programme and critically reviewing them from public health perspective.